2001
DOI: 10.1177/104687810103200301
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Game-Derived Learning in Total Enterprise Simulations

Abstract: This article reports a series of exploratory studies dealing with learning in total enterprise simulations. These studies had three purposes: (a) to examine the validity of simulations as learning tools, (b) to measure any relationships between learning about the simulation and economic performance in the game, (c) to discover if some players learn more than others from the same business gaming experience. For this research, learning emanated from the game’s structure and decision-making requirements. Learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 24 publications
2
36
1
3
Order By: Relevance
“…Third, we do not find evidence that playing the video-game would have a different relative effect on exam performance for males compared to females. Fourth, contrary to previous findings on business simulations (Anderson & Lawton, 1992;Gosen & Washbush, 2004;Washbush & Gosen, 2001), we find that game behavior and exam performance are related, and differently so for different types of learning and assessment: scores in multiple-choice questions are only correlated with game play elements; essay question scores are correlated with both watching instructional videos and engaging in game play; and, particularly for questions requiring deep understanding, synthesis and evaluation, using interactive graphs is also related to exam performance. Finally, students perceived the two learning tools similarly in terms of understanding instructions or usefulness, but as expected, they enjoyed the video-game considerably more.…”
contrasting
confidence: 82%
“…Third, we do not find evidence that playing the video-game would have a different relative effect on exam performance for males compared to females. Fourth, contrary to previous findings on business simulations (Anderson & Lawton, 1992;Gosen & Washbush, 2004;Washbush & Gosen, 2001), we find that game behavior and exam performance are related, and differently so for different types of learning and assessment: scores in multiple-choice questions are only correlated with game play elements; essay question scores are correlated with both watching instructional videos and engaging in game play; and, particularly for questions requiring deep understanding, synthesis and evaluation, using interactive graphs is also related to exam performance. Finally, students perceived the two learning tools similarly in terms of understanding instructions or usefulness, but as expected, they enjoyed the video-game considerably more.…”
contrasting
confidence: 82%
“…Washbush and Gosen (2001), for example, identified a total of 11 well-designed experimental studies of business simulations and concluded that the use of simulations improved learning by an average of 10% on pre-and post-training knowledge assessments. Wolfe (1997) included quasi-experimental studies in his review, but reached a similar conclusion that simulation gaming produced better learning than the use of business case studies.…”
Section: Evidence For the Effectiveness Of Simulation-based Trainingmentioning
confidence: 99%
“…It seems like that [students often say in the course] "we made it, it just happened, but we don"t know exactly why/how we got to the end". On the other hand, some explained that performers who struggled a lot learned more than high performers who struggled less (Washbush and Gosenpud, 1993;Wolfe and Chanin, 1993;Washbush and Gosen, 2001). From a pragmatic point of view this can be put another way: given simulation learning in a university setting is a means of attaining grades, the grade-seeking motivation, e.g.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…As a response to the commonsense suggestion: those who perform the best learn the most, some suggested that simulation-based learning correlates to performance positively (Teach, 1989;Wolfe and Deloach, 2009) but they are not linearly dependent. Numerous empirical outcomes indicate that the relationship between learning and performance seems weak (Anderson and Lawton, 1992;Wellington and Faria, 1992; Washbush and Gosen, 2001). Much evidence says that high performance maybe results in luck (Thorngate and Carroll, 1987;Burns et al, 1990).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation